Odpowiedź :
Odpowiedź:
[tex]a)\ \ 6\sqrt{56}-4\sqrt{8}+3\sqrt{18}+2\sqrt{32}=6\sqrt{4\cdot14}-4\sqrt{4\cdot2}+3\sqrt{9\cdot2}+2\sqrt{16\cdot2}=\\\\=6\cdot2\sqrt{14}-4\cdot2\sqrt{2}+3\cdot3\sqrt{2}+2\cdot4\sqrt{2}=12\sqrt{14}-8\sqrt{2}+9\sqrt{2}+8\sqrt{2}=\\\\=12\sqrt{14}+9\sqrt{2}[/tex]
[tex]b)\ \ 4\sqrt{75}-4\sqrt{48}+5\sqrt{27}=4\sqrt{25\cdot3}-4\sqrt{16\cdot3}+5\sqrt{9\cdot3}=\\\\=4\cdot5\sqrt{3}-4\cdot4\sqrt{3}+5\cdot3\sqrt{3}=20\sqrt{3}-16\sqrt{3}+15\sqrt{3}=19\sqrt{3}\\\\\\c)\ \ 6\sqrt{72}-4\sqrt{200}=6\sqrt{36\cdot2}-4\sqrt{100\cdot2}=6\cdot6\sqrt{2}-4\cdot10\sqrt{2}=\\\\=36\sqrt{2}-40\sqrt{2}=-4\sqrt{2}\\\\\\d)\ \ 13\sqrt{8}-2\sqrt{18}=13\sqrt{4\cdot2}-2\sqrt{9\cdot2}=13\cdot2\sqrt{2}-2\cdot3\sqrt{2}=26\sqrt{2}-6\sqrt{2}=20\sqrt{2}[/tex]